Attrition of health extension workers in Ethiopia: trends, regional variations and determinants - a mixed methods study of 15 years of experience - Habtamu Milkias Wolde; Merhawi Gebremedhin Tekle; Yibeltal Kiflie Alemayehu; Esie Gebrewahd Gebre; Alula M. Teklu (BMC, 2023)
Abstract Background Ensuring regular supervision, capacity building and motivation are crucial for the successful retention of health extension workers (HEWs). Failure in these aspects could increase the attrition rate of HEWs. To date, there has not been a comprehensive nationwide study on HEW attrition that could act as a source of evidence for policy makers. This study explored HEW attrition, including leaving the health sector entirely and its regional variation, trends and predictors of attrition out of the health system. Methods This study explored the attrition of HEWs from the beginning of the program until the end of 2018. A district-based mixed method study was conducted to review the personnel files of HEWs. A multistage sampling technique was employed to select 3,476 HEWs, and a probability weight was assigned for each observation. Descriptive statistics were calculated for the outcome and predictor variables. A logistic regression model was used to model attrition out of the health system. A qualitative study was conducted to understand the reasons why HEWs leave their jobs. Thematic analysis was performed using Nvivo version 12. Results The magnitude of attrition of HEWs was found to be 21.1% during the fifteen years of HEP implementation. Of the total 704 who left their job as an HEW, 530 (73%) left the health system altogether. Number of biological children [AOR = 0.61, 95% CI; 0.42-0.89], having an additional education [AOR = 8.34, 95% CI; 3.67-18.98], obtaining official recognition [AOR = 0.29, 95% CI; 0.10-0.83], administrative reprimand [AOR = 1.66, 95% CI; 1.07 -2. 56), distance between district health office and health post [AOR = 1.75, 95%CI; 1.18-2.59) and COC status [AOR = 2.06, 95%CI 1.39-3.06) were independent predictors of leaving the health sector. High regional variation in attrition was observed, ranging from 38.5% in Addis Ababa to just 6.1% in the Harari region. The trend of attrition has steadily increased over time, with a high of 1,999 attritions per 10,000 HEW in 2018. Psychosocial factors, administrative issues, career advancement incentives, and workplace-related problems were the themes that emerged from the qualitative study as reasons for attrition of HEWs. Conclusion Even though the magnitude of attrition was relatively low, there was high regional variation and incremental trends. Moreover, the out-of-health sector attrition is also high. Critically examining the HEP policy environment to increase the number of HEWs deployed per health post to reduce workload and improving HEW incentives, including career development, may assist in increasing HEW job satisfaction, which in turn could help to reduce attrition, including leaving the health sector.